Impedance study of giant dielectric permittivity in BaFe0.5Nb0.5O3 perovskite ceramic - Intatha U. (2014)
Single-phase BaFe0.5Nb0.5O3 (BFN) ceramics were prepared by solid-state reaction method and were characterized by X-ray Diffraction (XRD) technique. Then, impedance spectroscopy measurements were conducted in a frequency range from 100 Hz to 1 MHz and in a temperature range from 293 to 600 K. Relaxation phenomena of non-Debye type have been observed in the BFN ceramics, as confirmed by the Cole-Cole plots. The higher values of ε′ at the lower frequencies are explained on the basis of the Maxwell-Wagner (MW) polarization model. Complex impedance analysis enables us to separate the contributions from grains and grain boundaries of our samples. We found that at higher temperatures grain boundary resistance is higher than grain resistance, irrespective of composition. Crown Copyright © 2009.